Stefania Madej (1901–2010) z Dobronia. Stulatka i jej rodzina w świetle wywiadów, wspomnień i publikacji prasowych - Szkutnik, Piotr (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2012)
The biography tells the story of a long-lived Stefania Madej (1901–2010) living in Dobroń near Lodz. Stefania came from a peasant family. Her father worked hard all his life, thanks to which he became the owner of a medium-sized farm. Together with her siblings Stefania helped parents on the farm at the expense of her education. She married a farmer, still remaining in the provinces. When the World War II was over she cared for the sick husband and after his death, in the absence of children, gradually got rid of an agricultural land. Thus she remained destitute. However, state financial assistance and care of a niece let her live in good condition almost 109 years.